Urgensi Pembukuan Dalam Pengelolaan Keuangan Usaha Mikro - Baitii, Nur; Santi, Mila; Yudistira, Era; Listyarini, Rakhmawati (Jurnal Media Informatika, 2024)
Micro business, often face problems related to the lack of knowledge and understanding of business actors regarding the importance of financial management. Financial management is an important aspect for the company's progress. Financial management can be done through accounting. Accounting has always played an important role in entrepreneurship. Accounting allows micro business to obtain financial information when running their business. This qualitative research method aims to provide a more detailed explanation regarding financial management at the Kevin Sembako Store. This research technique will be limited to the accounting technique used, namely a simple accounting bookkeeping system. Good bookkeeping is the foundation for compiling financial reports such as profit and loss reports, capital changes reports, and balance sheets. Transaction data recorded neatly will make it easier to calculate income, expenses, assets, liabilities and capital. Through financial reports prepared based on accurate bookkeeping, business actors can easily understand the financial performance of their business. They can see whether their business is making profits or losses. Useful financial reports don't only cover quantitative aspects. Financial bookkeeping in a business or business is a strong foundation for building a business, which if not managed well will have fatal consequences for a business. From the research results, it can be concluded that the bookkeeping process is very important in managing a business.